The Change Process in Clients with High Needs - Buxton, Amberley R. M.; Rodger, Susan; Cummings, Anne L.; Leschied, Alan W. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examined the outcome of extended counselling sessions at a community counselling centre. Participants were 38 female and 7 male clients who were categorized as dealing with one of the following issues: trauma, multiple acute issues, complicated grief, or support while waiting for referral. Results showed a signifi cant lessening of symptoms and increase in coping skills between sessions 12 and 24 for all clients. Having previous counselling was signifi cantly related to magnitude of change on the Target Complaint change score. Through qualitative analyses, trauma and nontrauma clients described similar types of change from counselling: gaining insight, experiencing feelings, counselling relationship, self-growth, and new ways of being. However, some differences were apparent in the way that these categories were discussed by the trauma and nontrauma clients.